1993
DOI: 10.1007/bf01218423
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-biochemical assay for determination of nuclear steroid receptors during tamoxifen therapy

Abstract: The exact knowledge of hormone receptor status is critical for therapeutic strategies in hormone-dependent tumors. The influence of tamoxifen on estrogen receptor concentration has to be taken into account when evaluating results in tamoxifen-treated patients. We studied the receptor modulation of tumors xenotransplanted into nude mice (one breast and one endometrial carcinoma) after injection of 50 micrograms tamoxifen/mouse. To differentiate between unoccupied and occupied receptors, determinations were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is important to note that, as progestogens decrease the production of their own receptors 87 , continuous administration might decrease breast cell responsiveness in time. However, addition of oestrogen, or an oestrogenic substance (such as tamoxifen) will maintain the production of the progesterone receptor 88,89 .…”
Section: Action Of Progesterone: In Vitro Resultsmentioning
confidence: 99%
“…It is important to note that, as progestogens decrease the production of their own receptors 87 , continuous administration might decrease breast cell responsiveness in time. However, addition of oestrogen, or an oestrogenic substance (such as tamoxifen) will maintain the production of the progesterone receptor 88,89 .…”
Section: Action Of Progesterone: In Vitro Resultsmentioning
confidence: 99%
“…Of considerable interest is our finding that tamoxifen demonstrates uterine cell-type specificity in its ability to increase ER immunoreactivity in the luminal epithelium and that this effect is inhibited by ICI 182,780. Tamoxifen-induced up-regulation of ER has been demonstrated in MCF-7 cells [42, 431, in endometrial tumors grown in nude mice [44,45], and in human breast cancer [461. However, other studies have shown that tamoxifen either decreased ER levels or did not alter ER levels in breast cancer tissue [47,48].…”
Section: Discussionmentioning
confidence: 99%